Determining Noctuidae, Erebidae, Euteliidae and Nolidae (Lepidoptera, Noctuoidea) Families of Hasankeyf in Batman, Turkey - Abdulaziz Aykal; Erdem Seven (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2022)
The present study conducted on the Noctuoidea (Lepidoptera) fauna takes place in Hasankeyf, Batman prov., southeastern Turkey, between 2018-2020. Field based investigations were prominently carried out from sunset till sunrise due to the fact that the dominance of Noctuoidea species are regarded as nocturnal. Insect nets and UV light traps took over efficient roles in capturing noctuoid moths. The cycle of collecting those samples comprised of softening, stretching and identifying consecutively in accordance with the current literature. The results of the research indicated that there are 160 noctuoid moth species in the study area, 110 of which are newly recorded from Batman. The second report of Haemerosia vassilininei A. Bang-Haas, 1912 and endemic Dryobotodes glaucus Ronkay & Gyulai, 2006 in Turkey, are highlighted.